Investing in lagging regions is efficient: a local multipliers analysis of U.S. cities - Jasper van Dijk (European Regional Science Association (ERSA), 2015)
This paper illustrates the effect of employment in the tradable sector on employment in the non-tradable sector in the same city with a simple model. The model predicts a significant positive local employment multiplier that increases in size with the unemployment rate. It also predicts that the share of newly created jobs fulfilled by current inhabitants of a city increases with the unemployment rate. I test this model with data from the United States census between 1980 and 2000. I estimate that an additional 100 jobs in the tradable sector will increase employment in the non-tradable sector in the same city by employing an additional 81 current residents and 28 workers that move from other regions. I find that in a city with 3.7% unemployment the average local employment multiplier is 0.91 for current inhabitants and 0.60 for migrants. And in a city with 8.4% unemployment the average local employment multiplier is 1.82 for current inhabitants and 0.23 for migrants. These estimates are all consistent with the model and quantify the size of the effect. Finally a nonparametric estimation of the effect of the unemployment rate on the size of the local employment multiplier shows a neat fit to the functional form predicted by the model for both the increasing trend for current inhabitants and the decreasing trend for migrants. Governments can efficiently promote economic growth in cities by providing tax benefits to firms in the tradable sector that locate new plants or expand existing plants in cities with a high unemployment rate. This will increase growth of the tradable sector in cities with a high unemployment rate, which maximizes the positive impact of tradable sector growth on employment in the non-tradable sector. This can be a successful policy to stimulate growth in low growth regions, because cities in these regions tend to have higher unemployment rates. Governments already know that attracting tradable firm can benefit the local economy, for example: U.S. counties give tax cuts to attract tradable firms. Greenstone and Moretti [NBER (2003)] show this is not efficient and could result into all the rents being accrued by the firm, because counties bid against each other. The only gain for the winning county is based on private information, resulting in the firm going to the county that would benefit the most. The efficiency of attracting tradable firms can be increased if a more central government knows which regions would benefit the most from attracting tradable firms and would regulate the tax cuts offered based on this. As a result more benefits would go to the regions instead of the firms. The results from this paper could provide governments with the information needed to achieve this.
Keywords: F16; R15; R23; 330; Local labour market; multiplier; tradable; nontradable; unemployment